Analisis Penyusunan Laporan Keuangan Guna Mengembangkan Usaha Mikro,Kecil, dan Menengah (UMKM) dalam Etika Keuangan - Muhammad Ilham fiqri; Novia Grace Christin Limbong; Olivia Sembiring; Rebecca Putri Sihaloho; Rojelita Catrina Simarmata; Serly Sahfitri; Riza Indriani; Hilma Harmen; Gracella Rosnah S Hutagalung (MES Bogor, 2024)
Micro, small, and medium-sized financial reporting (UMKM) can build confidence and credibility in external actors, such as banks, investors, and governments, so that they can acquire the working capital and investment they need to thrive and thrive. If financial statements exist, they can serve as a